Comparison of low back pain prevalence in adults between pre-pandemic and pandemic periods and related biopsychosocial aspects - Kerolyne Soares Mayer; Betiane Moreira Pilling; Cláudia Tarragô Candotti (Fisioterapia e Pesquisa)
ABSTRACT The global health crisis resulting from the outbreak of the coronavirus (SARS-CoV-2) has led to social distancing, the repercussions of which on physical and mental health are still being assessed. This study aims to compare reported lower back pain in adults during the pre-pandemic and pandemic periods regarding intensity and frequency, as well as the risk of poor prognosis, disability, exposure to risk factors, beliefs, fears, and sitting posture in front of the computer. The sample of this retrospective study with a comparative ex post facto design consisted of 80 individuals with complaints of low back pain, divided by sex, age, height, and body mass-matched groups: 40 individuals in the pre-pandemic group (PPG) and 40 individuals in the pandemic group (PG), who were involved in university outreach projects. Data were collected using BackPEI-A, SBST, ODI, and FABQ questionnaires from 2016 to 2021. Mann–Whitney u-test and Student’s t -test were used for group comparisons (α <0.05). Comparison between PPG and PG showed no statistically significant differences regarding impairment, frequency, intensity of pain, sitting posture in front of the computer, exposure to risk factors, risk of poor prognosis, beliefs and fears, and disability.